The Difference of Phytoplankton Abundance from the Water around the Floating Cage Fish Culture Area and from the Area with No Cage, in the DAM Site of the Koto Panjang Reservoir - Shinta Permata Sari; Asmika H. Simarmata; Clemen Sihotang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstractIn floating cage fish culture activities, degradation of feed remain and fish feces willaffect the abundance of phytoplankton content in the surrounding area. A research aims tounderstand the difference of phytoplankton abundance in the water from the cage area and fromthe area that has no cage has been done from June – August 2014. In the Koto Panjang Dam,the floating cage fish culture is in the DAM site. Samplings were conducted 4 times, once/2weeks. There were 3 stations, namely 200 m upstream of the cage area (S1), in the cage area (S2)and 200 m downstream of the cage area (S3). In each station, water samples were collected from3 different depth, surface; 2 secchi and 4 secchi depths. Parameters measured were pH,phosphate, nitrate, free carbon dioxide, dissolved oxygen, transparancy, temperature and depth.Results shown the abundance of phytoplankton in the S1 was 1,068 – 8,226 cells/L ; in the S2was 500 – 3,720 cell/L; and in the S3 was 777 – 5,100 cells/L. The highest abundance ofPhytoplankton was in S1, while the lowest was in the cage area (S2). Phytoplankton abundancein the cage area was different compare to the area with no cage. Phytoplankton abundanceindicates that the DAM site area of the Koto Panjang can be classified as mesotrophic, especiallyin the area around the cage. Other water quality parameter measured were temperature: 29 oC –31oC; transparancy 1,98 m – 2,55 m; depth: 27 m – 40 m; pH: 5, free carbon dioxide: 4,49mg/L- 11,48 mg/L; dissolved oxygen: 3,28 – 7,17 mg/L; nitrate: 0,02 – 0,28 mg/L; phosphate :0,03 – 0,35 mg/L. the values of water quality parameters indicate that the water quality in theDAM site of the Koto Panjang is good and might be able to support the life of aquatic organismsin that area.Keywords: Phytoplankton, cage fish culture, Koto Panjang DAM